2021
DOI: 10.3310/phr09060
|View full text |Cite
|
Sign up to set email alerts
|

A school-based, peer-led programme to increase physical activity among 13- to 14-year-old adolescents: the GoActive cluster RCT

Abstract: Background Adolescent physical activity levels are low and are associated with rising disease risk and social disadvantage. The Get Others Active (GoActive) intervention was co-designed with adolescents and teachers to increase physical activity in adolescents. Objective To assess the effectiveness and cost-effectiveness of the school-based GoActive programme in increasing adolescents’ moderate-to-vigorous physical activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(41 citation statements)
references
References 145 publications
0
41
0
Order By: Relevance
“…Steady support and commitment from the school, and the enthusiastic project leaders, were cited as factors that helped intervention implementation. This highlighted the importance of stakeholder buy-in, as found in previous school-based PA initiatives [79,80]. Finally, tailoring interventions to the individual school context is important for scaling up [79,81].…”
Section: Strengthsmentioning
confidence: 83%
See 3 more Smart Citations
“…Steady support and commitment from the school, and the enthusiastic project leaders, were cited as factors that helped intervention implementation. This highlighted the importance of stakeholder buy-in, as found in previous school-based PA initiatives [79,80]. Finally, tailoring interventions to the individual school context is important for scaling up [79,81].…”
Section: Strengthsmentioning
confidence: 83%
“…Similar to Jago et al [ 52 ], stakeholders in this study recommended extra emphasis on enjoyment of classes when pitching the programme to increase participation. Using a parental/guardian, passive (opt-out) approach has allowed for greater recruitment of adolescents in previous low-risk, nonintrusive, school-based PA interventions [ 32 , 34 , 44 , 74 , 79 ], such as the Girls-Peer Activity (G-PACT) [ 32 ] (94% using passive consent vs 26% using active consent) and the GoActive programme [ 87 ] (78% using passive consent vs 23% using active consent). This refinement, however, is dependent on ethical approval from the institutional research ethics board and agreement from the participating school.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the main GoActive trail analysis reported no overall intervention effect on average daily MVPA 25. Subgroup analyses conducted as part of the trial evaluation reported a suggestion of a positive intervention effect among students of a low/middle-SEP. Across all MVPA outcomes, those of high-SEP appeared to benefit least when compared with low/middle-SEP students.…”
Section: Methodsmentioning
confidence: 91%